Uji Kelayakan Media Pembelajaran Interaktif Berbasis WEB Pada Pendidikan Kesehatan Reproduksi: Perspektif Ahli - Eldawaty Eldawaty; Anton Komaini; Mudjiran Mudjiran; Yanuar Kiram; Alwen Bentri; Monica Dara Pratiwi (Departemen Kesehatan Dan Rekreasi Fakultas Ilmu Keolahragaan Universitas Negeri Padang, 2025)
Reproductive health education plays a crucial role in enhancing students' understanding of the biological, psychological, and social aspects of reproductive health. However, conventional learning often faces challenges such as time constraints, a lack of interactivity, and limited access to materials. In the digital era, web-based learning media offer innovative solutions by utilizing interactive technologies, such as videos, quizzes, and discussion forums, to increase student engagement. This study aims to develop and test the feasibility of web-based interactive learning media for reproductive health education through expert validation. The research method used a Research and Development (R&D) approach, adopting the Borg & Gall model. The feasibility test phase involved six experts from the fields of materials, technology, evaluation, and education. The instruments used were a Likert-scale questionnaire and feedback sheets. The developed media included interactive features such as educational videos, quizzes, materials, and discussion forums. The expert validation results showed an excellent feasibility rating (87.44%). The findings of this study indicate that this web-based interactive learning media for reproductive health education is valid for use. Its main advantages lie in its flexibility, privacy, and appropriate media approach for sensitive topics. With these advantages, this media is not only valid but also has great potential to increase reproductive health literacy, combat misinformation and myths, and ultimately reduce risky behavior among students.